Atividades Econômicas, Geração de Emprego e Análise do Potencial de Desenvolvimento do Município de Campo Bom/RS - Marcos Paulo Dhein Griebeler (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
This article aims to identify possible chains that have potential to constitute a productive diversification option to the municipality of Campo Bom/RS. It was also sought to analyze these activities highlighting the importance of each one of them, raising potentialities and possible fragilities with the objective of contributing to the development of the municipality at a regional level. To do so, we used data from the Annual Social Information Relation (RAIS), the Municipal Agricultural Production Survey (PAM) and Municipal Livestock Research (PPM), and for its analysis, the regional specialization measure of Quocientes Locations (QLs). The study also presents a brief bibliographical review on the themes related to specialization and productive diversification. After conducting the research, it can be concluded that the leather-footwear chain is still the one that most employs and generates income for the citizens of Campo Bom. It was verified that productive diversification becomes viable, also, through other activities, as the textile chain.